2001
DOI: 10.1007/s004670100020
|View full text |Cite
|
Sign up to set email alerts
|

Puberty permits increased expression of renal transforming growth factor-?1 in experimental diabetes

Abstract: Prepubertal years of diabetes mellitus are relatively protected from clinical manifestations of nephropathy. Transforming growth factor-beta1 (TGF-beta1) is a major mediator of diabetic kidney disease. Its renal expression, translation, and activation change with sexual maturation in the normal rat. The role of TGF-beta1 in postpubertal susceptibility to diabetic renal hypertrophy was addressed in the present study. Male Sprague- Dawley rats were given streptozocin at 4 weeks of age (weanling) or 14 weeks of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…By acting via an autocrine or paracrine mechanism, this growth factor contributes to diabetic renal and glomerular hypertrophy (31). Our lab previously showed that sexually mature male DM rats had increased expression and activity of TGF-␤ 1 , along with increased glomerular hypertrophy, compared with prepubertal male DM rats (17). We have also demonstrated sexrelated differences in the renal TGF-␤ 1 system in normal rats (16).…”
mentioning
confidence: 91%
“…By acting via an autocrine or paracrine mechanism, this growth factor contributes to diabetic renal and glomerular hypertrophy (31). Our lab previously showed that sexually mature male DM rats had increased expression and activity of TGF-␤ 1 , along with increased glomerular hypertrophy, compared with prepubertal male DM rats (17). We have also demonstrated sexrelated differences in the renal TGF-␤ 1 system in normal rats (16).…”
mentioning
confidence: 91%
“…The onset of microalbuminuria, the earliest clinical manifestation of diabetic kidney disease, is so rare before puberty that screening is usually not recommended prior to the onset of sexual development [2,3]. Animal models also show differences in early renal and glomerular growth responses to the diabetic state [4][5][6][7][8][9]. Functional differences in diabetic kidney disease cannot be shown in rodent models, probably because of the short duration of prepubertal disease relative to the disease period required for renal dysfunction to develop.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the impact on kidney function of physiologic changes associated with pubertal growth and development in this population is unknown. These changes may accelerate the progression of calcineurin inhibitor induced nephrotoxicity as has been noted in other chronic nephropathies (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%